2020
DOI: 10.33084/bjop.v3i4.1583
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antidiabetic, and Anti-obesity Potential of Ipomoea reptans Poir Leaves

Abstract: Ipomoea reptans Poir or kangkung is a popular leafy vegetable, a favorite to people in Asian countries. However, limited information is available on their bioactivities. In the present study, the antioxidant, antidiabetic, and anti-obesity potential of I. reptans leaves were investigated. Different fractions (ethanol, ethyl acetate, and hexane) of I. reptans leaves were evaluated for their scavenging activity on DPPH radicals, whereas their reducing potential was investigated by cupric reducing antioxidant cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…The total phenolic acid of the ethanol extract of land kale obtained was 71.2420 ± 0.0791 mg/g GAE. The total phenolic results obtained in this study exceeded those reported in prior research by Mariani et al [22], where the value was 31 ± 0.849 mg/g GAE, and in the research conducted by Kurniawan et al [2], which reported a value of 0.86 mg/g GAE.…”
Section: Determination Extraction Phytochemical Screening and Determi...contrasting
confidence: 64%
See 1 more Smart Citation
“…The total phenolic acid of the ethanol extract of land kale obtained was 71.2420 ± 0.0791 mg/g GAE. The total phenolic results obtained in this study exceeded those reported in prior research by Mariani et al [22], where the value was 31 ± 0.849 mg/g GAE, and in the research conducted by Kurniawan et al [2], which reported a value of 0.86 mg/g GAE.…”
Section: Determination Extraction Phytochemical Screening and Determi...contrasting
confidence: 64%
“…Land kale contains vitamins and minerals that are good for human health and have secondary metabolite compounds in the form of phenolic acids, flavonoids, saponins, alkaloids, steroids, and triterpenoids [1]. Based on the content of secondary metabolites, kale plants are reported to have several activities, including antioxidant [2], anti-diabetic [3], anti-cancer [4], antiinflammatory, anti-microbial [5], anti-ulcers [6], and hypolipidemic agents [7].…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 value of the α-glucosidase inhibition activity of Ipomoea reptans leaf ethanolic extract was 0.26 mg/mL, and the value was 47.8 μg/mL in Olax imbricata Roxb. root methanol extract [ 32 , 33 ]. The IC 50 values of the α-glucosidase inhibitory activity of K. africana aqueous and ethanolic extracts were 486.92 and 157.99 μg/mL [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Determination of DPPH radical scavenging activity was conducted according to a previous method. 13 DPPH solution in ethanol (0.6 mM, 3 mL) was mixed with samples of different concentrations (1 mL in ethanol). The reaction mixture was incubated in the dark at room temperature for 30 mins, thereafter the absorbance was measured at 517 nm.…”
Section: Determination Of Dpph Radical Scavenging Activitymentioning
confidence: 99%